1978
DOI: 10.1007/bf00385079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water stress on abscisic acid levels in white lupin (Lupinus albus L.) fruit, leaves and phloem exudate

Abstract: Abscisic acid (ABA) was identified by combined gas liquid chromatography-mass spectrometry in sieve-tube exudate collected from the cut stylar ends of white lupin fruit. Water stress caused an increase in ABA levels in leaf, seed and pod tissues and phloem exudate. When compared with levels in extracts of these tissues, the concentration of ABA in sieve-tube sap was very high. It is suggested that ABA is actively transported out of mature leaves in the phloem and this finding is discussed in terms of the ABA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

1980
1980
1996
1996

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 11 publications
4
29
1
Order By: Relevance
“…However, translocation obstruction does not alter leaf water potentials (26), so if such treatments change ABA biosynthesis or catabolism, an alternative regulatory mechanism would be necessary to explain the observed changes in ABA level in the present study. Evidence of substantial ABA translocation from leaves into sinks has been demonstrated in experiments involving [14CJABA application to leaf blades of Phaseolus (1 1) and wheat (3,8), and ABA has been found in phloem exudate (12). We suggest that in the present study, ABA might have accumulated in leaves because its normal phloem export to other plant parts was slowed or blocked.…”
Section: Setter Brun and Brennersupporting
confidence: 59%
“…However, translocation obstruction does not alter leaf water potentials (26), so if such treatments change ABA biosynthesis or catabolism, an alternative regulatory mechanism would be necessary to explain the observed changes in ABA level in the present study. Evidence of substantial ABA translocation from leaves into sinks has been demonstrated in experiments involving [14CJABA application to leaf blades of Phaseolus (1 1) and wheat (3,8), and ABA has been found in phloem exudate (12). We suggest that in the present study, ABA might have accumulated in leaves because its normal phloem export to other plant parts was slowed or blocked.…”
Section: Setter Brun and Brennersupporting
confidence: 59%
“…In detached leaves the rise in [ABA] in response to water stress results largely from an increased rate of synthesis (Pierce & Raschke, 1981;Zeevaart, 1980;Murphy, 1984), while during rehydration synthesis is decreased and the rate of metabolism increased (Pierce & Raschke, 1981) leading to a rapid fall in [ABA]. In intact plants there is evidence for significant export of ABA from mature leaves (Goldbach & Goldbach, 1977;Zeevaart, 1977;Setter, Brun & Brenner, 1981;Zeevaart & Boyer, 1984) via phloem-mediated translocation (Hoad, 1973(Hoad, ,1978Zeevart, 1977;Hoad & Gaskin, 1980;Setter, Brun & Brenner, 1980;Weiler & Ziegler, 1981;Everat-Bourbouloux, 1982;Zeevaart & Boyer, 1984). However, both Hartung (1976) and Hoad (1978) have suggested that the export of ABA may be reduced during water stress.…”
Section: Introductionmentioning
confidence: 99%
“…In intact plants there is evidence for significant export of ABA from mature leaves (Goldbach & Goldbach, 1977;Zeevaart, 1977;Setter, Brun & Brenner, 1981;Zeevaart & Boyer, 1984) via phloem-mediated translocation (Hoad, 1973(Hoad, ,1978Zeevart, 1977;Hoad & Gaskin, 1980;Setter, Brun & Brenner, 1980;Weiler & Ziegler, 1981;Everat-Bourbouloux, 1982;Zeevaart & Boyer, 1984). However, both Hartung (1976) and Hoad (1978) have suggested that the export of ABA may be reduced during water stress.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial export of leaf-applied [14C]AbA has been observed in Phaseolus (7,10) and wheat (3,5) and AbA has been identified in phloem diffusates of white lupin (8) and Ricinus (24). If AbA is normally exported from leaves through the phloem, obstruction of such translocation might result in AbA accumulation in the leaves.…”
mentioning
confidence: 99%